Adhesive for non-aqueous battery and adhesive tape for non-aqueous battery
By using an adhesive of an acrylic polymer having acid functional groups and a crystalline resin in a non-aqueous battery, the problems of insufficient adhesiveness and greasiness in the prior art are solved, and efficient bonding and operability improvement in the non-aqueous electrolyte are achieved.
Patent Information
- Application Number
- CN202080031239.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-04-20
- Filing Date
- 2020-04-22
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2040-04-22
AI Technical Summary
The existing adhesive for non-aqueous battery is insufficient in the non-aqueous electrolyte, and it is easy to cause stickiness and overflow of the end surface of the adhesive tape, affecting the operationality of the battery assembly.
An adhesive that exhibits adhesiveness by crimping is used, including an acrylic polymer having an acid functional group and a crystalline resin having a melting point of 25°C or higher. The adhesive exhibits significant adhesiveness after heating, and controls the degree of adhesiveness and bond reliability by adjusting the structural ratio of the polymer and resin.
An adhesive with excellent adhesiveness and less stickiness in the non-aqueous electrolyte is realized, which avoids overflowing of the end surface of the adhesive tape and improves the operability and safety of battery assembly.
Smart Images

Figure CN114096631B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an adhesive for a non-aqueous battery and an adhesive tape for a non-aqueous battery. Background Art
[0002] In non-aqueous batteries such as lithium ion batteries that are sealed with non-aqueous electrolytes, adhesive tapes are used for the purpose of improving the packing properties of electrodes in the battery case, preventing short circuits between electrodes, etc. Such adhesive tapes are required to have reliable adhesion in non-aqueous electrolytes, and methods such as using highly hydrophobic adhesives (acrylic adhesives, rubber adhesives), making the adhesive contain an acid component, and adding additives such as tackifying resins to the adhesive have been studied (for example, Patent Document 1).
[0003] However, the adhesive that is intended to improve the bonding reliability in the non-aqueous electrolyte is usually soft, sticky, and overflows from the adhesive tape end surface, which causes a bad situation and reduced operability in the battery assembly process. In order to prevent this bad situation, it is possible to consider improving the crosslinking degree of the base polymer constituting the adhesive, reducing the thickness of the adhesive layer, reducing the amount of additives such as tackifying resin, etc. However, these means will reduce the bonding reliability in the non-aqueous electrolyte. That is, ensuring that the bonding reliability in the non-aqueous electrolyte and improving the operability in the battery assembly process present a relationship of one increasing while the other decreasing.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2013-140765 Summary of the invention
[0007] Problem that the invention aims to solve
[0008] The present invention has been made to solve the conventional problems, and its object is to provide a non-aqueous battery adhesive having excellent adhesion in a non-aqueous electrolyte and low stickiness, which can prevent overflow from the end surface of an adhesive tape when applied to the adhesive tape, and an adhesive tape containing the adhesive.
[0009] Solutions for solving problems
[0010] The binder for a nonaqueous battery of the present invention is a binder that exhibits adhesiveness by pressure bonding, and includes an acrylic polymer having an acid functional group and a crystalline resin having a melting point of 25° C. or higher.
[0011] In one embodiment, the nonaqueous battery binder develops adhesiveness by heating.
[0012] In one embodiment, the acrylic polymer having an acid functional group has a structural unit a derived from an alkyl (meth)acrylate having a linear or branched alkyl group having 4 or more carbon atoms.
[0013] In one embodiment, the content ratio of the structural unit a is 50 parts by weight or more based on 100 parts by weight of the acrylic polymer having an acid functional group.
[0014] In one embodiment, the crystalline resin is a polyolefin-based resin.
[0015] In one embodiment, the polyolefin-based resin is a maleic anhydride-modified polyolefin-based resin, a maleic acid-modified polyolefin-based resin, or an acrylic acid-modified polyolefin-based resin.
[0016] In one embodiment, the nonaqueous battery binder includes a C5-based petroleum resin and / or a C9-based petroleum resin.
[0017] According to another aspect of the present invention, there is provided a pressure-sensitive adhesive tape for a non-aqueous battery. The pressure-sensitive adhesive tape for a non-aqueous battery includes the above-mentioned pressure-sensitive adhesive for a non-aqueous battery.
[0018] In one embodiment, the pressure-sensitive adhesive tape for a nonaqueous battery includes a substrate and a pressure-sensitive adhesive layer disposed on at least one side of the substrate, wherein the pressure-sensitive adhesive layer contains the pressure-sensitive adhesive for a nonaqueous battery.
[0019] In one embodiment, the substrate is formed of at least one selected from the group consisting of polyacrylate, polyurethane, polyimide, aromatic polyamide, polyamide, ethylene-vinyl alcohol copolymer, polyetherimide, polyvinylidene fluoride, polyester, polypropylene, polyethylene, and polyphenylene sulfide.
[0020] In one embodiment, a release film is provided on the side of the pressure-sensitive adhesive layer opposite to the substrate.
[0021] In one embodiment, the adhesive layer is disposed on one side of the substrate, and the other adhesive layer is disposed on the other side of the substrate.
[0022] According to another aspect of the present invention, there is provided a nonaqueous battery comprising the above-mentioned pressure-sensitive adhesive tape for a nonaqueous battery.
[0023] Effects of the Invention
[0024] According to the present invention, there can be provided a non-aqueous battery adhesive having excellent adhesiveness in a non-aqueous electrolyte solution and low stickiness, which can prevent overflow from the end surface of an adhesive tape when applied to the adhesive tape, and an adhesive tape comprising the same. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a schematic cross-sectional view of a pressure-sensitive adhesive tape for a non-aqueous battery according to one embodiment of the present invention.
[0026] Figure 2 This is a schematic cross-sectional view of a pressure-sensitive adhesive tape for a non-aqueous battery according to another embodiment of the present invention. DETAILED DESCRIPTION
[0027] A. Binders for non-aqueous batteries
[0028] The adhesive for non-aqueous batteries of the present invention is an adhesive that exhibits adhesiveness by crimping, and comprises an acrylic polymer having an acid functional group and a crystalline resin having a melting point of 25°C or more. In the present invention, by using an acrylic polymer having an acid functional group and the above-mentioned crystalline resin in combination, an adhesive having less stickiness (specifically, having an appropriate probe adhesion value) and exhibiting excellent adhesiveness in a non-aqueous electrolyte, and whose adhesiveness is not easily reduced over time, can be obtained. If such an adhesive is used, an adhesive tape having excellent functionality in preventing internal short circuits and excellent operability in the battery assembly process can be obtained. In addition, the above-mentioned adhesive tape can be suitably used for joining components used in non-aqueous electrolytes (e.g., separators, electrodes, outer packaging materials (metal cans, bags, etc.). In addition, the above-mentioned adhesive tape can be configured as a double-sided adhesive tape, which can be suitably used for joining metal materials to metal materials, joining non-metallic materials to non-metallic materials, and joining metal materials to non-metallic materials. Furthermore, in the adhesive of the present invention, the balance between the stickiness and the bonding reliability can be easily controlled by adjusting the structure of the acrylic polymer having an acid functional group (e.g., monomer components, molecular weight), the structure of the crystalline resin, the content ratio of the acrylic polymer having an acid functional group and the crystalline resin, etc.
[0029] The adhesive may be one that exhibits adhesiveness at room temperature (25° C.) or one that exhibits adhesiveness by heating (e.g., 100° C. to 200° C.). An adhesive that exhibits adhesiveness by heating may exhibit adhesiveness when cooled to room temperature after heating.
[0030] A-1. Acrylic polymers having acid functional groups
[0031] Examples of the acrylic polymer having an acid functional group include an acrylic polymer containing a structural unit derived from one or more kinds of alkyl (meth)acrylates and a structural unit derived from a monomer having an acid functional group.
[0032] In the above-mentioned adhesive, the content ratio of the acrylic polymer with an acid functional group is preferably 7 to 95 parts by weight relative to 100 parts by weight of the solid content in the adhesive, more preferably 15 to 90 parts by weight, further preferably 20 to 85 parts by weight, and particularly preferably 40 to 85 parts by weight. The content of the acrylic polymer with an acid functional group can be set to an appropriate amount according to the desired probe adhesion value, adhesion, etc. It should be noted that the above-mentioned adhesive may include an acrylic polymer without an acid functional group in addition to the acrylic polymer with an acid functional group, and may not include an acrylic polymer without an acid functional group.
[0033] The content of the structural unit derived from the alkyl (meth)acrylate is preferably 50 to 99 parts by weight, more preferably 70 to 98 parts by weight, and even more preferably 80 to 98 parts by weight, based on 100 parts by weight of the acrylic polymer having an acid functional group.
[0034] The alkyl (meth)acrylate preferably has a linear or branched alkyl group having 1 to 24 carbon atoms (more preferably 3 to 20, further preferably 4 to 12, particularly preferably 4 to 8).
[0035] Examples of the alkyl (meth)acrylate include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, pentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, octyl (meth)acrylate, nonyl (meth)acrylate, decyl (meth)acrylate, and eicosyl (meth)acrylate.
[0036] In one embodiment, the acrylic polymer having an acid functional group has a structural unit a derived from an alkyl (meth)acrylate, wherein the alkyl (meth)acrylate has a linear or branched alkyl group having 4 or more carbon atoms (preferably 4 to 12, more preferably 4 to 8), and the content of the structural unit a is 50 parts by weight or more (preferably 50 to 99 parts by weight, more preferably 70 to 98 parts by weight, and further preferably 80 to 98 parts by weight) relative to 100 parts by weight of the acrylic polymer having an acid functional group. If an acrylic polymer having an acid functional group containing a predetermined amount or more of the structural unit a is used, an adhesive having excellent bonding reliability in a non-aqueous electrolyte can be obtained.
[0037] In one embodiment, as the above-mentioned alkyl (meth)acrylate, an alkyl (meth)acrylate having a branched alkyl group can be used. If an alkyl (meth)acrylate having a branched alkyl group is used, the effect of the present invention is particularly significant. The number of carbon atoms of the above-mentioned branched alkyl group is preferably 4 or more, more preferably 4 to 12, and further preferably 4 to 8. An alkyl (meth)acrylate having a straight-chain alkyl group and an alkyl (meth)acrylate having a branched alkyl group can also be used in combination. In addition, as the alkyl (meth)acrylate, an alkyl (meth)acrylate having a branched alkyl group can be used alone.
[0038] In one embodiment, in the acrylic polymer having an acid functional group, the content ratio of the structural unit derived from the (meth)acrylic acid alkyl ester having a branched alkyl group is preferably 50 to 100 parts by weight, more preferably 70 to 100 parts by weight, and even more preferably 80 to 100 parts by weight, relative to 100 parts by weight of the structural unit derived from the (meth)acrylic acid alkyl ester (i.e., 100 parts by weight of the total amount of the (meth)acrylic acid alkyl ester having a linear alkyl group and the (meth)acrylic acid alkyl ester having a branched alkyl group).
[0039] As the (meth) acrylate alkyl ester having a branched alkyl group, for example, isobutyl (meth) acrylate, sec-butyl (meth) acrylate, tert-butyl (meth) acrylate, 2-ethylhexyl (meth) acrylate, isooctyl (meth) acrylate, isononyl (meth) acrylate, isodecyl (meth) acrylate, 2-ethylbutyl (meth) acrylate, 2-methylbutyl (meth) acrylate, etc. can be listed. Among them, 2-ethylhexyl (meth) acrylate, isooctyl (meth) acrylate, isononyl (meth) acrylate or isodecyl (meth) acrylate is preferred, and 2-ethylhexyl (meth) acrylate is more preferred. If 2-ethylhexyl (meth) acrylate is used, an adhesive having particularly excellent bonding reliability in a non-aqueous electrolyte can be obtained.
[0040] As the acid functional group of the acrylic polymer having an acid functional group, for example, a carboxyl group, an anhydride group, a phosphoric acid group, a sulfonic acid group, etc. can be listed. Therefore, as the monomer having the above-mentioned acid functional group, for example, a carboxyl group-containing monomer, an anhydride group-containing monomer, a phosphoric acid group-containing monomer, a sulfonic acid group-containing monomer, etc. can be listed. Among them, a carboxyl group-containing monomer is preferred. If a carboxyl group-containing monomer is used, it is easy to show adhesion to a metal plate, and in addition, it also has the following characteristics in terms of design / production: it is easy to copolymerize with other acrylic monomers, and the polymer formed by copolymerization is easy to crosslink.
[0041] Examples of the carboxyl group-containing monomer include (meth)acrylic acid, carboxyethyl acrylate, carboxypentyl acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, etc. Among them, acrylic acid is preferred.
[0042] The content of the structural unit derived from the monomer having an acid functional group is preferably 1.5 to 20 parts by weight, more preferably 1.8 to 15 parts by weight, and further preferably 2 to 10 parts by weight, based on 100 parts by weight of the acrylic polymer having an acid functional group.
[0043] The acrylic polymer having an acid functional group may contain a structural unit derived from other monomers copolymerizable with the above-mentioned alkyl (meth)acrylate and / or monomer having an acid functional group, for the purpose of modifying cohesion, heat resistance, crosslinking properties, etc., as required. Examples of such other monomers include hydroxyl-containing monomers such as hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate, hydroxyhexyl (meth)acrylate, hydroxyoctyl (meth)acrylate, hydroxydecyl (meth)acrylate, hydroxylauryl (meth)acrylate, and (4-hydroxymethylcyclohexyl)methyl methacrylate; (N-substituted)amide monomers such as (meth)acrylamide, N,N-dimethyl (meth)acrylamide, N-butyl (meth)acrylamide, N-hydroxymethyl (meth)acrylamide, and N-hydroxymethylpropane (meth)acrylamide; (Meth) acrylate aminoalkyl ester monomers such as aminoethyl (meth)acrylate, N,N-dimethylaminoethyl (meth)acrylate, and tert-butylaminoethyl (meth)acrylate; (meth) acrylate alkoxyalkyl ester monomers such as methoxyethyl (meth)acrylate and ethoxyethyl (meth)acrylate; maleimide monomers such as N-cyclohexylmaleimide, N-isopropylmaleimide, N-laurylmaleimide, and N-phenylmaleimide; N-methylitaconimide, N-ethylitaconimide, N-butylitaconimide, N-octylitaconimide, N-2-ethylhexyl Itaconimide monomers such as itaconimide, N-cyclohexyl itaconimide, and N-lauryl itaconimide; succinimide monomers such as N-(meth)acryloyloxymethylenesuccinimide, N-(meth)acryloyl-6-oxyhexamethylenesuccinimide, and N-(meth)acryloyl-8-oxyoctamethylenesuccinimide; vinyl acetate, vinyl propionate, N-vinylpyrrolidone, methylvinylpyrrolidone, vinylpyridine, vinylpiperidone, vinylpyrimidine, vinylpiperazine, vinylpyrazine, vinylpyrrole, vinylimidazole, vinyloxazole, vinylmorpholine, N- Vinyl monomers such as vinyl carboxylic acid amides, styrene, α-methylstyrene, and N-vinyl caprolactam; cyanoacrylate monomers such as acrylonitrile and methacrylonitrile; epoxy-containing acrylic monomers such as glycidyl (meth)acrylate; glycol acrylate monomers such as polyethylene glycol (meth)acrylate, polypropylene glycol (meth)acrylate, methoxyethylene glycol (meth)acrylate, and methoxypolypropylene glycol (meth)acrylate; acrylate monomers having heterocyclic rings, halogen atoms, silicon atoms, etc., such as tetrahydrofurfuryl (meth)acrylate, fluoro (meth)acrylate, and silicone (meth)acrylate;Hexanediol di(meth)acrylate, (poly)ethylene glycol di(meth)acrylate, (poly)propylene glycol di(meth)acrylate, neopentyl glycol di(meth)acrylate, pentaerythritol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, dipentaerythritol hexa(meth)acrylate, epoxy acrylate, polyester acrylate, urethane acrylate and other multifunctional monomers; olefin monomers such as isoprene, butadiene, isobutylene; vinyl ether monomers such as vinyl ether, etc. These monomer components can be used alone or in combination of two or more. ;
[0044] The content of the structural unit derived from the other monomer is preferably 20 parts by weight or less, more preferably 10 parts by weight or less, and further preferably 5 parts by weight or less, based on 100 parts by weight of the acrylic polymer having an acid functional group.
[0045] The weight average molecular weight of the acrylic polymer having an acid functional group is preferably 300,000 to 2,000,000, and more preferably 500,000 to 1,500,000. The weight average molecular weight can be measured by GPC (solvent: THF).
[0046] A-2. Crystalline resin
[0047] As described above, the binder of the present invention contains a crystalline resin. The crystalline resin refers to a resin having a clear endothermic peak (half-value width within 15° C.) in a differential calorimetry curve measured by a differential scanning calorimeter (DSC).
[0048] The content of the crystalline resin in the binder is preferably 3 to 90 parts by weight, more preferably 10 to 85 parts by weight, and further preferably 15 to 80 parts by weight, based on 100 parts by weight of the solid content in the binder.
[0049] The melting point of the crystalline resin is 25° C. or higher, more preferably 40° C. or higher, further preferably 60° C. to 120° C., and particularly preferably 60° C. to 100° C. Within this range, a less sticky adhesive can be obtained. The melting point can be measured by differential scanning calorimetry (DSC).
[0050] The weight average molecular weight of the crystalline resin is preferably 50,000 to 1,500,000, and more preferably 70,000 to 1,000,000.
[0051] The crystallinity of the crystalline resin is preferably 10% or more, more preferably 20% or more. Typically, the crystallinity can be measured by differential scanning calorimetry (DSC).
[0052] In one embodiment, the crystalline resin is a polyolefin-based resin. Examples of the polyolefin resin include ethylene-α-olefin copolymers such as ethylene homopolymers, ethylene-propylene copolymers, ethylene-1-butene copolymers, ethylene-1-hexene copolymers, ethylene-1-octene copolymers, ethylene-1-heptene copolymers, ethylene-1-octene copolymers, ethylene-1-nonene copolymers, ethylene-1-decene copolymers, ethylene-1-undecene copolymers, ethylene-1-dodecene copolymers, ethylene-1-tridecene copolymers, ethylene-1-tetradecene copolymers, ethylene-1-pentadecene copolymers, ethylene-1-hexadecene copolymers, ethylene-1-heptadecene copolymers, ethylene-1-octadecene copolymers, ethylene-1-nonadecene copolymers, and ethylene-1-eicosene copolymers; ethylene-vinyl acetate copolymers, ethylene-vinyl propionate copolymers, and other ethylene-unsaturated carboxylic acid alkyl ester copolymers such as ethylene-methyl methacrylate copolymers, ethylene-methyl acrylate copolymers, ethylene-ethyl acrylate copolymers, and ethylene-butyl acrylate copolymers; and propylene resins.
[0053] In one embodiment, as the above-mentioned crystalline resin, a crystalline polypropylene resin can be used. Crystalline polypropylene resin can be a homopolymer or a copolymer obtained from propylene and a monomer copolymerizable with propylene. As monomers copolymerizable with propylene, alpha-olefins such as ethylene, 1-butene, 1-pentene, 1-hexene, 1-octene, 1-decene, 4-methyl-1-pentene, and 3-methyl-1-pentene can be listed. In the crystalline polypropylene resin, the content ratio of the structural unit derived from propylene is preferably 60 mol% to 99 mol%, more preferably 65 mol% to 99 mol%, and further preferably 70 mol% to 99 mol%. In the crystalline polypropylene resin, the content ratio of the structural unit derived from alpha-olefin is preferably 1 mol% to 15 mol%, more preferably 1 mol% to 10 mol%.
[0054] In one embodiment, as the above-mentioned crystalline resin, a modified polyolefin resin can be used. If a modified polyolefin resin is used, an adhesive in which the phase separation of the crystalline resin and the acrylic polymer having an acid functional group is suppressed and an adhesive layer with less bleeding and excellent transparency can be obtained. As a modified polyolefin resin, maleic anhydride-modified polyolefin resin, maleic acid-modified polyolefin resin, acrylic acid-modified polyolefin resin, etc. can be preferably used. Specifically, resins obtained by maleic anhydride modification, maleic acid modification or acrylic acid modification of the above-mentioned polyolefin resin can be listed. Among them, maleic anhydride polyolefin resin is preferred, and maleic anhydride-modified propylene resin is more preferred. As a specific example of maleic anhydride-modified propylene resin, a resin obtained by maleic anhydride modification of the above-mentioned crystalline polypropylene resin can be listed. The modification rate of the modified polyolefin resin is preferably 1% to 5% by weight, and more preferably 1.5% to 2% by weight.
[0055] A-3. Additives
[0056] The above-mentioned adhesive may contain any and appropriate additives as required. As such additives, for example, crosslinking agents, tackifiers, plasticizers (for example, trimellitic acid ester plasticizers, pyromellitic acid ester plasticizers), pigments, dyes, fillers, antioxidants, conductive materials, ultraviolet light absorbers, light stabilizers, release regulators, softeners, surfactants, flame retardants, antioxidants, solvents, etc. may be cited. In addition, the above-mentioned adhesive may contain any and appropriate solvents.
[0057] As the above-mentioned tackifier, any and appropriate tackifier can be used. As the tackifier, for example, a tackifying resin can be used. As a specific example of the tackifying resin, rosin-based tackifying resins (for example, unmodified rosin, modified rosin, rosin phenol resin, rosin ester resin, etc.), terpene-based tackifying resins (for example, terpene resins, terpene phenol resins, styrene-modified terpene resins, aromatic modified terpene resins, hydrogenated terpene resins), hydrocarbon-based tackifying resins (for example, aliphatic hydrocarbon resins, aliphatic cyclic hydrocarbon resins, aromatic hydrocarbon resins (for example, styrene resins, xylene resins, etc.), aliphatic-aromatic petroleum resins, aliphatic-alicyclic petroleum resins, hydrogenated hydrocarbon resins, coumarone resins, coumarone indene resins, etc.), phenol-based tackifying resins (for example, alkylphenol resins, xylene formaldehyde resins, resol phenolic, novolac, etc.), ketone-based tackifying resins, polyamide-based tackifying resins, epoxy-based tackifying resins, elastic system tackifying resins, etc. can be listed.
[0058] In one embodiment, in the above-mentioned adhesive, a C5-based petroleum resin and / or a C9-based petroleum resin may be used as a thickener. When these thickeners are used, an adhesive having a highly reliable adhesive force in a non-aqueous electrolyte can be obtained.
[0059] The softening point of the tackifier is preferably 70° C. to 200° C., and more preferably 80° C. to 190° C. Within this range, a pressure-sensitive adhesive layer having appropriately adjusted storage modulus and loss modulus can be obtained.
[0060] The content of the tackifier is preferably 5 to 50 parts by weight, more preferably 10 to 40 parts by weight, based on 100 parts by weight of the total amount of the acrylic polymer having an acid functional group and the crystalline resin having a melting point of 25° C. or higher.
[0061] Examples of the crosslinking agent include isocyanate crosslinking agents, epoxy crosslinking agents, melamine crosslinking agents, and peroxide crosslinking agents, as well as urea crosslinking agents, metal alkoxide crosslinking agents, metal chelate crosslinking agents, metal salt crosslinking agents, carbodiimide crosslinking agents, oxazoline crosslinking agents, aziridine crosslinking agents, and amine crosslinking agents. Among them, isocyanate crosslinking agents, epoxy crosslinking agents, and metal chelate crosslinking agents are preferred.
[0062] Specific examples of the isocyanate crosslinking agent include lower aliphatic polyisocyanates such as 1,4-butanediisocyanate and hexamethylene diisocyanate; alicyclic isocyanates such as cyclopentylene diisocyanate, cyclohexylene diisocyanate, and isophorone diisocyanate; aromatic isocyanates such as 2,4-toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, and xylylene diisocyanate; isocyanate adducts such as trimethylolpropane / toluene diisocyanate trimer adduct (manufactured by Nippon Polyurethane Industries, Ltd., trade name "CORONATE L"), trimethylolpropane / hexamethylene diisocyanate trimer adduct (manufactured by Nippon Polyurethane Industries, Ltd., trade name "CORONATE HL"), and isocyanurate of hexamethylene diisocyanate (manufactured by Nippon Polyurethane Industries, Ltd., trade name "CORONATE HX"), etc. The content of the isocyanate crosslinking agent can be set to an arbitrary and appropriate amount according to the desired adhesive force and elastic modulus, and is typically 0.1 to 20 parts by weight, more preferably 0.5 to 10 parts by weight, relative to 100 parts by weight of the total amount of the acrylic polymer having an acid functional group and the crystalline resin having a melting point of 25° C. or higher.
[0063] Examples of the epoxy crosslinking agent include N,N,N',N'-tetraglycidyl-m-xylylenediamine, diglycidyl aniline, 1,3-bis(N,N-glycidylaminomethyl)cyclohexane (manufactured by Mitsubishi Gas Chemical Co., Ltd., trade name "TETRAD C"), 1,6-hexanediol diglycidyl ether (manufactured by Kyoeisha Chemical Co., Ltd., trade name "EPOLIGHT 1600"), neopentyl glycol diglycidyl ether (manufactured by Kyoeisha Chemical Co., Ltd., trade name "EPOLIGHT 1500NP"), ethylene glycol diglycidyl ether (manufactured by Kyoeisha Chemical Co., Ltd., trade name "EPOLIGHT 40E"), propylene glycol diglycidyl ether (manufactured by Kyoeisha Chemical Co., Ltd., trade name "EPOLIGHT 70P"), polyethylene glycol diglycidyl ether (manufactured by NOF Corporation, trade name "EPIOLIGHT 1500NP"), and polyoxyethylene glycol diglycidyl ether. E-400”), polypropylene glycol diglycidyl ether (manufactured by NOF Corporation, trade name “EPIOL P-200”), sorbitol polyglycidyl ether (manufactured by Nagase ChemteX, trade name “DENACOL EX-611”), glycerol polyglycidyl ether (manufactured by Nagase ChemteX, trade name “DENACOL EX-314”), pentaerythritol polyglycidyl ether, polyglycerol polyglycidyl ether (manufactured by Nagase ChemteX, trade name “DENACOL EX-512”), sorbitan polyglycidyl ether, trimethylolpropane polyglycidyl ether, adipic acid diglycidyl ester, phthalic acid diglycidyl ester, triglycidyl-tris(2-hydroxyethyl)isocyanurate, resorcinol diglycidyl ether, bisphenol-S-diglycidyl ether, epoxy resins having two or more epoxy groups in the molecule, and the like. The content of the epoxy crosslinking agent can be set to an arbitrary and appropriate amount according to the desired adhesive force and elastic modulus, and is typically 0.01 to 10 parts by weight, more preferably 0.03 to 5 parts by weight, relative to 100 parts by weight of the total amount of the acrylic polymer having an acid functional group and the crystalline resin having a melting point of 25° C. or higher.
[0064] As the metal chelate crosslinking agent, for example, a metal chelate compound whose metal atom is aluminum, zirconium, titanium, zinc, iron, tin, etc. Among them, an aluminum chelate compound or a titanium chelate compound is preferred.
[0065] Examples of the aluminum chelate compound include diisopropoxyaluminum monooleate acetoacetate, monoisopropoxyaluminum dioleate acetoacetate, monoisopropoxyaluminum monoethyl acetoacetate, diisopropoxyaluminum monolauryl acetoacetate, diisopropoxyaluminum monostearyl acetoacetate, diisopropoxyaluminum monoisostearyl acetoacetate, mono-N-lauroyl-β-aluminoxy monolauryl monoisopropoxyaluminum acetoacetate, aluminum tris(acetylacetonate), aluminum acetylacetonate bis(ethyl acetoacetate), aluminum acetylacetonate bis(isobutyl acetoacetate), aluminum acetylacetonate bis(2-ethylhexyl acetoacetate), aluminum acetylacetonate bis(dodecyl acetoacetate), and aluminum acetylacetonate bis(oleyl acetoacetate).
[0066] Examples of the titanium chelate compound include bis(acetylacetonate)diisopropoxytitanium, titanium tetra-n-butyrate, titanium tetra-2-ethylhexanoate, titanium tetraacetylacetonate, bis(ethyl acetylacetonate)diisopropoxytitanium, and titanium octyl glycolate.
[0067] Examples of other metal chelate compounds include zirconium tetraacetylacetonate and zirconium monoacetylacetonate tributoxylate.
[0068] The above-mentioned metal chelate cross-linking agents may be used alone or in combination of two or more.
[0069] The content of the metal chelate crosslinking agent can be set to an arbitrary and appropriate amount according to the desired adhesive force and elastic modulus, and is typically 0.01 to 10 parts by weight, more preferably 0.03 to 7 parts by weight, and further preferably 0.05 to 5 parts by weight, relative to 100 parts by weight of the total amount of the acrylic polymer having an acid functional group and the crystalline resin having a melting point of 25° C. or higher.
[0070] B. Adhesive tape for non-aqueous batteries
[0071] Figure 1 It is a schematic cross-sectional view of an adhesive tape for non-aqueous batteries (hereinafter also referred to as an adhesive tape) based on an embodiment of the present invention. The adhesive tape 100 comprises a substrate 10 and an adhesive layer 20 disposed on at least one side (both sides in the illustrated example) of the substrate 10. The adhesive layer 20 comprises the adhesive described in the above-mentioned item A. Although not shown in the figure, the above-mentioned adhesive tape may be provided with a release film on the outside of the adhesive layer (i.e., the surface of the adhesive layer on the side opposite to the substrate) for the purpose of protecting the adhesive surface until it is used.
[0072] Figure 2It is a schematic cross-sectional view of an adhesive tape for non-aqueous batteries based on other embodiments of the present invention. The adhesive tape 200 comprises: a substrate 10, an adhesive layer 20 disposed on one side of the substrate 10, and another adhesive layer 30 disposed on the other side of the substrate. The adhesive layer 20 comprises the adhesive described in item A above. The other adhesive layer 30 comprises any and appropriate adhesive (e.g., an acrylic adhesive, a rubber adhesive) other than the adhesive described in item A. Although not shown in the figure, the above-mentioned adhesive tape may be provided with a release film on the outside of the adhesive layer and / or other adhesive layers (i.e., the surface of the adhesive layer and / or other adhesive layers on the opposite side of the substrate) for the purpose of protecting the adhesive surface until it is used.
[0073] The pressure-sensitive adhesive tape may exhibit adhesiveness at room temperature (25° C.) or may exhibit adhesiveness when heated. A pressure-sensitive adhesive tape that exhibits adhesiveness when heated may exhibit adhesiveness when heated and then cooled to room temperature.
[0074] The adhesive force at 25°C when the adhesive layer of the adhesive tape of the present invention is attached to aluminum foil is preferably 0.5N / 10mm or more, more preferably 0.8N / 10mm~20N / 10mm, and further preferably 1N / 10mm~10N / 10mm. If it is in this range, an adhesive tape suitable for non-aqueous battery use can be made. In this specification, the adhesive force refers to the adhesive force measured by the method based on JIS Z0237:2000, and the adhesive tape is attached to the aluminum foil by a 2kg roller back and forth once, and after being placed at 25°C for 30 minutes, the adhesive tape is peeled off and measured under the conditions of a peeling angle of 180° and a peeling speed (tensile speed) of 300mm / min. It should be noted that when the adhesive tape is an adhesive tape that exhibits adhesiveness by heating, the adhesive tape and the aluminum foil are bonded by a bonding operation at a temperature at which the adhesive tape exhibits adhesiveness (for example, 130°C, 0.4 MPa, 5 seconds), and the adhesive force measured after cooling to 25°C is equivalent to the above-mentioned adhesive force.
[0075] The thickness of the pressure-sensitive adhesive tape is preferably 5 μm to 200 μm, more preferably 15 μm to 150 μm, and even more preferably 30 μm to 100 μm.
[0076] B-1. Adhesive layer
[0077] The adhesive layer includes the adhesive described in the above section A.
[0078] The thickness of the pressure-sensitive adhesive layer is preferably 1 μm to 100 μm, more preferably 3 μm to 80 μm, and even more preferably 5 μm to 50 μm.
[0079] The probe adhesive strength value of the adhesive layer at 25° C. is preferably 500 g or less, more preferably 400 g or less, further preferably 340 g or less, and particularly preferably 10 g to 300 g. The method for measuring the probe adhesive strength value is described below.
[0080] B-2. Base material
[0081] As the substrate, a resin film is preferably used. As the resin constituting the resin film, for example, polyacrylate, polyurethane, polyimide, aromatic polyamide, polyamide, ethylene-vinyl alcohol copolymer, polyetherimide, polyvinylidene fluoride, polyester, polypropylene, polyethylene, polyphenylene sulfide, etc. can be listed. These resins can be used alone or in combination of two or more.
[0082] The thickness of the substrate is preferably 1 μm to 100 μm, more preferably 5 μm to 100 μm, more preferably 10 μm to 70 μm, and even more preferably 15 μm to 50 μm.
[0083] In one embodiment, a nonaqueous battery comprising the above-mentioned adhesive tape for a nonaqueous battery is provided. The adhesive tape for a nonaqueous battery is used for purposes such as improving the packing properties of electrodes in a battery case and preventing short circuits between electrodes.
[0084] Example
[0085] The present invention is described in detail below by way of examples, but the present invention is not limited to these examples. The evaluation methods in the examples are as follows. In the examples, "parts" and "%" are by weight unless otherwise specified.
[0086] (1) Adhesion
[0087] The adhesive tapes obtained in the examples and comparative examples were attached to the surface of the aluminum foil under the following conditions to obtain a test body. It should be noted that the adhesive tapes of Examples 10, 11, 13, 14, Comparative Examples 6 and 7 are heat-bonding adhesive tapes, and therefore, they were pressed only under heating (130° C.), and the other adhesive tapes were pressed at room temperature (25° C.) and heating (130° C.).
[0088] The force (N / 10 mm) required to peel the pressure-sensitive adhesive tape from the aluminum foil surface was measured for the obtained test piece using a precision universal testing machine (trade name "Autograph AG-I", manufactured by Shimadzu Corporation) under the following conditions as the pressure-sensitive adhesive strength of the pressure-sensitive adhesive tape.
[0089] (Crimp conditions)
[0090] Normal temperature crimping: 2kg roller is pressed back and forth once.
[0091] Heating and pressing: Pressing was performed at 0.4 MPa for 5 seconds with the surface temperature of the bonding device set at 130°C.
[0092] (Peeling conditions)
[0093] Temperature: Normal temperature (25℃)
[0094] Peeling speed: 300mm / min
[0095] Peeling angle: 180°
[0096] (2) Adhesion in non-aqueous electrolyte
[0097] The test body prepared in the above (1) was immersed in an electrolyte solution containing 1.0 mol / L lithium hexafluorophosphate as an electrolyte and ethylene carbonate and diethyl carbonate in a volume ratio (ethylene carbonate: diethyl carbonate) of 1:2 at 80°C for 72 hours, and the adhesive tape was visually observed to see if there was any floating or peeling. Thereafter, the test body without the adhesive tape peeled off was lifted from the electrolyte solution, washed with ethanol, and the force (N / 10mm) required to peel the adhesive tape from the aluminum foil surface was measured by the same method as in the above (1) as the adhesive force in the non-aqueous electrolyte.
[0098] (3) Probe adhesion value
[0099] The probe adhesion value was measured on the surface of the adhesive layer by a probe adhesion method. The probe adhesion value was measured under the following conditions using an adhesion tester (manufactured by RHESCA).
[0100] (Measurement conditions)
[0101] Temperature: 25℃
[0102] Probe material: SUS
[0103] Probe shape: cylindrical (5mmφ)
[0104] Pressurization (compression) speed: 30mm / min
[0105] Measurement (detachment) speed: 30 mm / min
[0106] Preload: 100gf
[0107] Pressurization (compression) time: 1 second
[0108] (4) Haze value
[0109] The haze value of the pressure-sensitive adhesive tape was measured using a haze meter (model: HM-150, manufactured by Murakami Color Laboratory) by injecting incident light from the pressure-sensitive adhesive layer side.
[0110] (5) Adhesive overflow test
[0111] The adhesive tape cut into 10 mm squares was pressure-bonded to a SUS plate under the same conditions as in (1) above.
[0112] Thereafter, the tape was pressed under the following conditions, and the amount of adhesive protruding from the end surface of the tape was evaluated.
[0113] Pressing conditions: 0.4 MPa × 6 hours, with the surface temperature of the hot press device set to 130°C.
[0114] [Example 1]
[0115] Into a four-necked flask equipped with a stirring blade, a thermometer, a nitrogen inlet tube, and a condenser, 2-ethylhexyl acrylate / acrylic acid (95 parts by weight / 5 parts by weight), 0.2 parts by weight of benzoyl peroxide as an initiator, and 120 parts by weight of ethyl acetate were added, and nitrogen was introduced while slowly stirring. The liquid temperature in the flask was maintained at approximately 60° C., and a polymerization reaction was carried out for about 6 hours to obtain an acrylic copolymer (1) having a weight average molecular weight of 1.3 million.
[0116] To 75 parts by weight of the acrylic copolymer (1), 25 parts by weight of a maleic anhydride-modified propylene-butene copolymer resin (manufactured by Toyobo Co., Ltd., trade name "TOYOTAC PMA-L", weight average molecular weight of 75,000, melting point of 70°C) as a modified olefin resin and 2 parts by weight of an isocyanate crosslinking agent (manufactured by Tosoh Corporation, trade name "CORONATE L") were added, and the mixture was diluted with toluene to prepare an adhesive (1) having a solid content of 15%.
[0117] The obtained adhesive was applied onto a substrate (polypropylene film, manufactured by Toray Industries, Ltd., trade name "TORAYFAN", thickness: 30 μm) so that the thickness of the adhesive layer after drying was 10 μm, thereby obtaining an adhesive tape (1).
[0118] The obtained pressure-sensitive adhesive tape was subjected to the evaluations of (1) to (5) above. The results are shown in Table 1.
[0119] [Example 2]
[0120] In the same manner as in Example 1, an acrylic copolymer (1) was obtained.
[0121] To 75 parts by weight of the acrylic copolymer (1), 25 parts by weight of a maleic anhydride-modified propylene-butene copolymer resin (manufactured by Toyobo Co., Ltd., trade name "TOYOTAC PMA-L", weight average molecular weight 75,000, melting point 70°C) as a modified olefin resin, 30 parts by weight of a hydrogenated derivative of a C9-based petroleum resin (manufactured by Arakawa Chemical Industries, Ltd., trade name "Arkon P-125", hydrogenation rate: 95%, softening point: 125°C), and 2 parts by weight of an isocyanate crosslinking agent (manufactured by Tosoh Corporation, trade name "CORONATEL") were added, and the mixture was diluted with toluene to prepare an adhesive (2) having a solid content of 15%.
[0122] The obtained adhesive was applied onto a substrate (polypropylene film, manufactured by Toray Industries, Ltd., trade name "TORAYFAN", thickness: 30 μm) so that the thickness of the adhesive layer after drying was 10 μm, thereby obtaining an adhesive tape (2).
[0123] The obtained pressure-sensitive adhesive tape was subjected to the evaluations of (1) to (5) above. The results are shown in Table 1.
[0124] [Example 3]
[0125] In the same manner as in Example 1, an acrylic copolymer (1) was obtained.
[0126] To 75 parts by weight of the acrylic copolymer (1), 25 parts by weight of a maleic anhydride-modified propylene-butene copolymer resin (manufactured by Toyobo Co., Ltd., trade name "TOYOTAC PMA-T", weight average molecular weight: 75,000, melting point: 90°C) as a modified olefin resin and 2 parts by weight of an isocyanate crosslinking agent (manufactured by Tosoh Corporation, trade name "CORONATE L") were added, and the mixture was diluted with toluene to prepare an adhesive (3) having a solid content of 15%.
[0127] The obtained adhesive was applied onto a substrate (polypropylene film, manufactured by Toray Industries, Ltd., trade name "TORAYFAN", thickness: 12 μm) so that the thickness of the adhesive layer after drying was 15 μm, thereby obtaining an adhesive tape (3).
[0128] The obtained pressure-sensitive adhesive tape was subjected to the evaluations of (1) to (5) above. The results are shown in Table 1.
[0129] [Example 4]
[0130] In the same manner as in Example 1, an acrylic copolymer (1) was obtained.
[0131] To 85 parts by weight of the acrylic copolymer (1), 15 parts by weight of a maleic anhydride-modified propylene-butene copolymer resin (manufactured by Toyobo Co., Ltd., trade name "TOYOTAC PMA-T", weight average molecular weight: 75,000, melting point: 90°C) as a modified olefin resin and 2 parts by weight of an isocyanate crosslinking agent (manufactured by Tosoh Corporation, trade name "CORONATE L") were added, and the mixture was diluted with toluene to prepare an adhesive (4) having a solid content of 15%.
[0132] The obtained adhesive was applied onto a substrate (polypropylene film, manufactured by Toray Industries, Ltd., trade name "TORAYFAN", thickness: 12 μm) so that the thickness of the adhesive layer after drying was 5 μm, thereby obtaining an adhesive tape (4).
[0133] The obtained pressure-sensitive adhesive tape was subjected to the evaluations of (1) to (5) above. The results are shown in Table 1.
[0134] [Example 5]
[0135] A pressure-sensitive adhesive tape (5) was prepared in the same manner as in Example 4 except that a 6-μm-thick polyester film (manufactured by DuPont Hongji Films Foshan Co. Ltd., trade name “KLBD”) was used as the substrate and the pressure-sensitive adhesive layer had a thickness of 3 μm.
[0136] The obtained pressure-sensitive adhesive tape was subjected to the evaluations of (1) to (5) above. The results are shown in Table 1.
[0137] [Example 6]
[0138] In the same manner as in Example 1, an acrylic copolymer (1) was obtained.
[0139] To 75 parts by weight of the acrylic copolymer (1), 25 parts by weight of a maleic anhydride-modified propylene-butene copolymer resin (manufactured by Toyobo Co., Ltd., trade name "TOYOTAC PMA-Lz", weight average molecular weight: 100,000, melting point: 70°C) as a modified olefin resin and 2 parts by weight of an isocyanate crosslinking agent (manufactured by Tosoh Corporation, trade name "CORONATE L") were added, and the mixture was diluted with toluene to prepare an adhesive (5) having a solid content of 15%.
[0140] The obtained adhesive was applied onto a substrate (polypropylene film, manufactured by Toray Industries, Ltd., trade name "TORAYFAN", thickness: 30 μm) so that the thickness of the adhesive layer after drying was 10 μm, thereby obtaining an adhesive tape (6).
[0141] The obtained pressure-sensitive adhesive tape was subjected to the evaluations of (1) to (5) above. The results are shown in Table 1.
[0142] [Example 7]
[0143] Into a four-necked flask equipped with a stirring blade, a thermometer, a nitrogen inlet tube, and a condenser, 2-ethylhexyl acrylate / acrylic acid (90 parts by weight / 10 parts by weight), 0.2 parts by weight of benzoyl peroxide as an initiator, and 120 parts by weight of ethyl acetate were added, and nitrogen was introduced while slowly stirring. The liquid temperature in the flask was maintained at approximately 60° C., and a polymerization reaction was carried out for about 6 hours to obtain an acrylic copolymer (2) having a weight average molecular weight of 1.2 million.
[0144] To 85 parts by weight of the acrylic copolymer (2), 15 parts by weight of a maleic anhydride-modified propylene-butene copolymer resin (manufactured by Toyobo Co., Ltd., trade name "TOYOTAC PMA-L", weight average molecular weight: 75,000, melting point: 70°C) as a modified olefin resin and 2 parts by weight of an isocyanate crosslinking agent (manufactured by Tosoh Corporation, trade name "CORONATE L") were added, and the mixture was diluted with toluene to prepare an adhesive (6) having a solid content of 15%.
[0145] The obtained adhesive was applied onto a substrate (polyimide film, manufactured by Toray Industries, trade name “KAPTON 100H”, thickness: 25 μm) so that the thickness of the adhesive layer after drying was 10 μm, thereby obtaining an adhesive tape (7).
[0146] The obtained pressure-sensitive adhesive tape was subjected to the evaluations of (1) to (5) above. The results are shown in Table 1.
[0147] [Example 8]
[0148] Into a four-necked flask equipped with a stirring blade, a thermometer, a nitrogen inlet tube, and a condenser, 2-ethylhexyl acrylate / acrylic acid (100 parts by weight / 2 parts by weight), 0.2 parts by weight of benzoyl peroxide as an initiator, and 230 parts by weight of ethyl acetate were added, and nitrogen was introduced while slowly stirring. The liquid temperature in the flask was maintained at approximately 60° C., and a polymerization reaction was carried out for about 6 hours to obtain an acrylic copolymer (3) having a weight average molecular weight of 650,000.
[0149] To 70 parts by weight of the acrylic copolymer (3), 30 parts by weight of a maleic anhydride-modified propylene-butene copolymer resin (manufactured by Toyobo Co., Ltd., trade name "TOYOTAC PMA-L", weight average molecular weight: 75,000, melting point: 70°C) as a modified olefin resin and 2 parts by weight of an isocyanate crosslinking agent (manufactured by Tosoh Corporation, trade name "CORONATE L") were added, and the mixture was diluted with toluene to prepare an adhesive (7) having a solid content of 15%.
[0150] The obtained adhesive was applied onto a substrate (polypropylene film, manufactured by Toray Industries, trade name "TORAYFAN", thickness: 30 μm) so that the thickness of the adhesive layer after drying was 10 μm, thereby obtaining an adhesive tape (8).
[0151] The obtained pressure-sensitive adhesive tape was subjected to the evaluations of (1) to (5) above. The results are shown in Table 1.
[0152] [Example 9]
[0153] Into a four-necked flask equipped with a stirring blade, a thermometer, a nitrogen inlet tube, and a condenser, n-butyl acrylate / acrylic acid (95 parts by weight / 5 parts by weight), 0.2 parts by weight of 2,2'-azobisisobutyronitrile as an initiator, and 233 parts by weight of ethyl acetate were added, and nitrogen was introduced while slowly stirring. The liquid temperature in the flask was maintained at approximately 60°C, and a polymerization reaction was carried out for about 6 hours to obtain an acrylic copolymer (4) having a weight average molecular weight of 700,000.
[0154] To 85 parts by weight of the acrylic copolymer (4), 15 parts by weight of a maleic anhydride-modified propylene-butene copolymer resin (manufactured by Toyobo Co., Ltd., trade name "TOYOTAC PMA-L", weight average molecular weight: 75,000, melting point: 70°C) as a modified olefin resin and 2 parts by weight of an isocyanate crosslinking agent (manufactured by Tosoh Corporation, trade name "CORONATE L") were added, and the mixture was diluted with toluene to prepare an adhesive (8) having a solid content of 15%.
[0155] The obtained adhesive was applied on a substrate (polypropylene film, manufactured by Toray Industries, Ltd., trade name "TORAYFAN", thickness: 30 μm) so that the thickness of the adhesive layer after drying was 10 μm, thereby obtaining an adhesive tape (9).
[0156] The obtained pressure-sensitive adhesive tape was subjected to the evaluations of (1) to (5) above. The results are shown in Table 1.
[0157] [Example 10]
[0158] In the same manner as in Example 7, an acrylic copolymer (2) was obtained.
[0159] To 25 parts by weight of the acrylic copolymer (2), 75 parts by weight of a maleic anhydride-modified propylene-butene copolymer resin (manufactured by Toyobo Co., Ltd., trade name "TOYOTAC PMA-L", weight average molecular weight: 75,000, melting point 70°C) as a modified olefin resin and 2 parts by weight of an isocyanate crosslinking agent (manufactured by Tosoh Corporation, trade name "CORONATE L") were added, and the mixture was diluted with toluene to prepare an adhesive (9) having a solid content of 15%.
[0160] The obtained adhesive was applied onto a substrate (polypropylene film, manufactured by Toray Industries, Ltd., trade name "TORAYFAN", thickness: 12 μm) so that the thickness of the adhesive layer after drying was 3 μm, thereby obtaining an adhesive tape (10).
[0161] The obtained pressure-sensitive adhesive tape was subjected to the evaluations of (1) to (5) above. The results are shown in Table 1.
[0162] [Example 11]
[0163] In the same manner as in Example 1, an acrylic copolymer (1) was obtained.
[0164] To 15 parts by weight of the acrylic copolymer (1), 85 parts by weight of a maleic anhydride-modified propylene-butene copolymer resin (manufactured by Toyobo Co., Ltd., trade name "TOYOTAC PMA-T", weight average molecular weight: 75,000, melting point: 90°C) as a modified olefin resin and 2 parts by weight of an isocyanate crosslinking agent (manufactured by Tosoh Corporation, trade name "CORONATE L") were added, and the mixture was diluted with toluene to prepare an adhesive (10) having a solid content of 15%.
[0165] The obtained adhesive was applied onto a substrate (polypropylene film, manufactured by Toray Industries, Ltd., trade name "TORAYFAN", thickness: 30 μm) so that the thickness of the adhesive layer after drying was 10 μm, thereby obtaining an adhesive tape (11).
[0166] The obtained pressure-sensitive adhesive tape was subjected to the evaluations of (1) to (5) above. The results are shown in Table 1.
[0167] [Example 12]
[0168] In the same manner as in Example 1, an acrylic copolymer (1) was obtained.
[0169] To 85 parts by weight of the acrylic copolymer (1), 15 parts by weight of a maleic anhydride-modified propylene-butene copolymer resin (manufactured by Toyobo Co., Ltd., trade name "TOYOTAC PMA-L", weight average molecular weight 75,000, melting point 70°C) as a modified olefin resin and 0.5 parts by weight of an aluminum chelate crosslinking agent (trade name "Aluminum Chelate A", manufactured by Kawaken Fine Chemicals Co., Ltd.) were added, and the mixture was diluted with toluene to prepare an adhesive (11) having a solid content of 15%.
[0170] The obtained adhesive was applied onto a substrate (polypropylene film, manufactured by Toray Industries, Ltd., trade name "TORAYFAN", thickness: 12 μm) so that the thickness of the adhesive layer after drying was 10 μm, thereby obtaining an adhesive tape (12).
[0171] The obtained pressure-sensitive adhesive tape was subjected to the evaluations of (1) to (5) above. The results are shown in Table 1.
[0172] [Example 13]
[0173] In the same manner as in Example 1, an acrylic copolymer (1) was obtained.
[0174] To 15 parts by weight of the acrylic copolymer (1), 85 parts by weight of a maleic anhydride-modified propylene-butene copolymer resin (manufactured by Toyobo Co., Ltd., trade name "TOYOTAC PMA-L", weight average molecular weight 75,000, melting point 70°C) as a modified olefin resin and 0.2 parts by weight of an aluminum chelate crosslinking agent (trade name "Aluminum Chelate A", manufactured by Kawaken Fine Chemicals Co., Ltd.) were added, and the mixture was diluted with toluene to prepare an adhesive (12) having a solid content of 15%.
[0175] The obtained adhesive was applied onto a substrate (polypropylene film, manufactured by Toray Industries, Ltd., trade name "TORAYFAN", thickness: 12 μm) so that the thickness of the adhesive layer after drying was 5 μm, thereby obtaining an adhesive tape (13).
[0176] The obtained pressure-sensitive adhesive tape was subjected to the evaluations of (1) to (5) above. The results are shown in Table 1.
[0177] [Example 14]
[0178] In the same manner as in Example 1, an acrylic copolymer (1) was obtained.
[0179] To 25 parts by weight of the acrylic copolymer (1), 75 parts by weight of a maleic anhydride-modified propylene-butene copolymer resin (manufactured by Toyobo Co., Ltd., trade name "TOYOTAC PMA-T", weight average molecular weight 75,000, melting point 90°C) as a modified olefin resin and 0.1 parts by weight of an epoxy crosslinking agent (manufactured by Mitsubishi Gas Chemical Co., Ltd., trade name "TETRAD C") were added, and the mixture was diluted with toluene to prepare an adhesive (13) having a solid content of 15%.
[0180] The obtained adhesive was applied onto a substrate (polypropylene film, manufactured by Toray Industries, Ltd., trade name "TORAYFAN", thickness: 12 μm) so that the thickness of the adhesive layer after drying was 5 μm, thereby obtaining an adhesive tape (14).
[0181] The obtained pressure-sensitive adhesive tape was subjected to the evaluations of (1) to (5) above. The results are shown in Table 1.
[0182] [Comparative Example 1]
[0183] In the same manner as in Example 1, an acrylic copolymer (1) was obtained.
[0184] To 100 parts by weight of the acrylic copolymer (1), 18 parts by weight of a modified rosin resin (manufactured by HARIMA CHEMICALS GROUP, INC., trade name "HARIESTER KT-3") and 2 parts by weight of an isocyanate crosslinking agent (manufactured by Tosoh Corporation, trade name "CORONATE L") were added, and the mixture was diluted with toluene to prepare an adhesive (C1) having a solid content of 15%.
[0185] The obtained adhesive was applied on a substrate (polypropylene film, manufactured by Toray Industries, Ltd., trade name "TORAYFAN", thickness: 30 μm) so that the thickness of the adhesive layer after drying was 10 μm, thereby obtaining an adhesive tape (C1).
[0186] The obtained pressure-sensitive adhesive tape was subjected to the evaluations of (1) to (5) above. The results are shown in Table 2.
[0187] [Comparative Example 2]
[0188] In the same manner as in Example 1, an acrylic copolymer (1) was obtained.
[0189] 2 parts by weight of an isocyanate crosslinking agent (manufactured by Tosoh Corporation, trade name "CORONATE L") was added to 100 parts by weight of the acrylic copolymer (1), and the mixture was diluted with toluene to prepare an adhesive (C2) having a solid content of 15%.
[0190] The obtained adhesive was applied onto a substrate (polypropylene film, manufactured by Toray Industries, Ltd., trade name “TORAYFAN”, thickness: 30 μm) so that the thickness of the adhesive layer after drying was 10 μm, thereby obtaining an adhesive tape (C2).
[0191] The obtained pressure-sensitive adhesive tape was subjected to the evaluations of (1) to (5) above. The results are shown in Table 2.
[0192] [Comparative Example 3]
[0193] In the same manner as in Example 1, an acrylic copolymer (1) was obtained.
[0194] 0.5 parts by weight of an epoxy crosslinking agent (trade name "TETRAD C" manufactured by Mitsubishi Gas Chemical Co., Ltd.) was added to 100 parts by weight of the acrylic copolymer (1), and the mixture was diluted with toluene to prepare an adhesive (C3) having a solid content of 15%.
[0195] The obtained adhesive was applied on a substrate (polypropylene film, manufactured by Toray Industries, Ltd., trade name "TORAYFAN", thickness: 30 μm) so that the thickness of the adhesive layer after drying was 10 μm, thereby obtaining an adhesive tape (C3).
[0196] The obtained pressure-sensitive adhesive tape was subjected to the evaluations of (1) to (5) above. The results are shown in Table 2.
[0197] [Comparative Example 4]
[0198] In the same manner as in Example 9, an acrylic copolymer (4) was obtained.
[0199] To 100 parts by weight of the acrylic copolymer (4), 30 parts by weight of a terpene phenolic resin (manufactured by Yasuhara Chemical Co., Ltd., trade name "YS POLYSTER S-145", softening point: about 145°C), 2 parts by weight of an isocyanate crosslinking agent (manufactured by Tosoh Corporation, trade name "CORONATE L"), and 0.03 parts by weight of an epoxy crosslinking agent (manufactured by Mitsubishi Gas Chemical Co., Ltd., trade name "TETRAD C") were added, and the mixture was diluted with toluene to prepare an adhesive (C4) having a solid content of 15%.
[0200] The obtained adhesive was applied onto a substrate (polypropylene film, manufactured by Toray Industries, Ltd., trade name "TORAYFAN", thickness: 30 μm) so that the thickness of the adhesive layer after drying was 10 μm, thereby obtaining an adhesive tape (C4).
[0201] The obtained pressure-sensitive adhesive tape was subjected to the evaluations of (1) to (5) above. The results are shown in Table 2.
[0202] [Comparative Example 5]
[0203] Into a four-necked flask equipped with a stirring blade, a thermometer, a nitrogen inlet tube, and a condenser, 2-ethylhexyl acrylate / 2-hydroxyethyl acrylate (100 parts by weight / 4 parts by weight), 0.2 parts by weight of 2,2'-azobisisobutyronitrile as an initiator, and 233 parts by weight of ethyl acetate were added, and nitrogen was introduced while slowly stirring. The liquid temperature in the flask was maintained at approximately 60°C, and a polymerization reaction was carried out for about 6 hours to obtain an acrylic copolymer (5) having a weight average molecular weight of 550,000.
[0204] To 85 parts by weight of the acrylic copolymer (5), 15 parts by weight of a maleic anhydride-modified propylene-butene copolymer resin (manufactured by Toyobo Co., Ltd., trade name "TOYOTAC PMA-L", weight average molecular weight: 75,000, melting point: 70°C) as a modified olefin resin and 2 parts by weight of an isocyanate crosslinking agent (manufactured by Tosoh Corporation, trade name "CORONATE L") were added, and the mixture was diluted with toluene to prepare an adhesive (C5) having a solid content of 15%.
[0205] The obtained adhesive was applied on a substrate (polypropylene film, manufactured by Toray Industries, Ltd., trade name "TORAYFAN", thickness 30 μm) so that the thickness of the adhesive layer after drying was 10 μm, thereby obtaining an adhesive tape (C5).
[0206] The obtained pressure-sensitive adhesive tape was subjected to the evaluations of (1) to (5) above. The results are shown in Table 2.
[0207] [Comparative Example 6]
[0208] In the same manner as in Comparative Example 5, an acrylic copolymer (5) was obtained.
[0209] To 25 parts by weight of the acrylic copolymer (5), 75 parts by weight of a maleic anhydride-modified propylene-butene copolymer resin (manufactured by Toyobo Co., Ltd., trade name "TOYOTAC PMA-L", weight average molecular weight: 75,000, melting point: 70°C) as a modified olefin resin and 2 parts by weight of an isocyanate crosslinking agent (manufactured by Tosoh Corporation, trade name "CORONATE L") were added, and the mixture was diluted with toluene to prepare an adhesive (C6) having a solid content of 15%.
[0210] The obtained adhesive was applied on a substrate (polypropylene film, manufactured by Toray Industries, Ltd., trade name "TORAYFAN", thickness: 30 μm) so that the thickness of the adhesive layer after drying was 10 μm, thereby obtaining an adhesive tape (C6).
[0211] The obtained pressure-sensitive adhesive tape was subjected to the evaluations of (1) to (5) above. The results are shown in Table 2.
[0212] [Comparative Example 7]
[0213] 100 parts by weight of a maleic anhydride-modified propylene-butene copolymer resin (manufactured by Toyobo Co., Ltd., trade name "TOYOTAC PMA-L", weight average molecular weight: 75,000, melting point: 70°C) as a modified olefin resin was dissolved in toluene to prepare an adhesive (C7) having a solid content of 15%.
[0214] The obtained adhesive was applied on a substrate (polypropylene film, manufactured by Toray Industries, Ltd., trade name "TORAYFAN", thickness: 30 μm) so that the thickness of the adhesive layer after drying was 10 μm, thereby obtaining an adhesive tape (C7).
[0215] The obtained pressure-sensitive adhesive tape was subjected to the evaluations of (1) to (5) above. The results are shown in Table 2.
[0216] [Table 1]
[0217]
[0218] [Table 2]
[0219]
[0220] Description of Reference Numerals
[0221] 10. Substrate
[0222] 20 Adhesive layer
[0223] 100 Adhesive tape for non-aqueous batteries
Claims
1. A non-aqueous battery adhesive, which is an adhesive that exhibits adhesiveness by pressure bonding, comprising an acrylic polymer having an acid functional group and a crystalline resin having a melting point of 25° C. or more, The crystalline resin is a polyolefin resin, The polyolefin resin is maleic anhydride modified polyolefin resin, maleic acid modified polyolefin resin or acrylic acid modified polyolefin resin. In the binder, the content of the crystalline resin is 15 parts by weight to 80 parts by weight based on 100 parts by weight of solid content in the binder. 2 . The non-aqueous battery binder according to claim 1 , which exhibits adhesiveness when heated.
3. The non-aqueous battery binder according to claim 1 or 2, wherein The acrylic polymer having an acid functional group has a structural unit a derived from an alkyl (meth)acrylate having a linear or branched alkyl group having 4 or more carbon atoms.
4. The non-aqueous battery binder according to claim 3, wherein The content ratio of the structural unit a is 50 parts by weight or more based on 100 parts by weight of the acrylic polymer having an acid functional group. 5 . The non-aqueous battery binder according to claim 1 , comprising a C5-based petroleum resin and / or a C9-based petroleum resin.
6. The binder for non-aqueous batteries according to claim 1 or 2, wherein In the adhesive, the content of the acrylic polymer having an acid functional group is 40 parts by weight to 95 parts by weight based on 100 parts by weight of the solid content in the adhesive. 7 . A pressure-sensitive adhesive tape for a non-aqueous battery, comprising the pressure-sensitive adhesive for a non-aqueous battery according to claim 1 .
8. The adhesive tape for a non-aqueous battery according to claim 7, comprising a substrate and an adhesive layer disposed on at least one side of the substrate, The binder layer comprises the binder for a non-aqueous battery according to any one of claims 1 to 6.
9. The adhesive tape for a non-aqueous battery according to claim 8, wherein The substrate is formed of at least one selected from the group consisting of polyacrylate, polyurethane, polyimide, aromatic polyamide, polyamide, ethylene-vinyl alcohol copolymer, polyetherimide, polyvinylidene fluoride, polyester, polypropylene, polyethylene, and polyphenylene sulfide.
10. The adhesive tape for non-aqueous batteries according to claim 8 or 9, wherein A release film is provided on the side of the pressure-sensitive adhesive layer opposite to the substrate.
11. The adhesive tape for non-aqueous batteries according to claim 8 or 9, wherein The adhesive layer is disposed on one side of the substrate. Another adhesive layer is disposed on the other side of the substrate. 12 . A non-aqueous battery comprising the pressure-sensitive adhesive tape for a non-aqueous battery according to claim 7 .
Citation Information
Patent Citations
Pressure-sensitive adhesive tape for battery and battery using the pressure-sensitive adhesive tape
JP2013140765A
Pressure-sensitive adhesive tape for battery and battery using the pressure-sensitive adhesive tape
CN102653662A
Shatterproofing member with hardenable pressure-sensitive adhesive layer
CN103547645A
Adhesive based on non-polar polyolefin resin
CN106905892A
Adhesive composition and adhesive article
CN1509323A